Scrutinizing All the Factors in Antimicrobial Resistance - Shuman, Jill (MD Conference Express, 2015)
While antibiotic resistance is a growing problem across the globe, it is not clear whether the predicted trajectory of resistance has been adequately evaluated. Blind adherence to strict practice guidelines regarding antibiotics may put patients at harm, and researchers are urged to appraise the evidence underlying clinical recommendations.